Future skills for Industry 4.0 integration and innovative learning for continuing engineering education - Azofeifa, Jose Daniel; Rueda-Castro, Valentina; Camacho-Zuñiga, Claudia; Chans, Guillermo M.; Membrillo-Hernández, Jorge; Caratozzolo, Patricia (Frontiers in Education, 2024)
Introduction This research explores leveraging Industry 4.0 technologies and best practices to address the challenges faced by Continuing Engineering Education (CEE) in Higher Education, ensuring its sustainability and relevance. CEE is essential for engineers' continuous professional growth and adaptability, especially in an era marked by swift technological progress and changing job requirements. CEE must adapt to rapid technological advancements and evolving workforce demands. Nevertheless, traditional pedagogical methods often lag behind the needs of modern engineering professionals. Methods Through a case study, this study aims to show how skills visualization allows the creation of comparisons between professional scenarios to enhance the effectiveness and efficiency of CEE programs. To achieve this goal, we utilized a platform based on the KSA taxonomy, which enables the visualization of skills and supports creating personalized and adaptive learning. Results Our results demonstrate the transformative potential of integrating new technologies and learning approaches in CEE programs. By leveraging Industry 4.0 technologies, developing personalized learning experiences, and embracing Education 4.0 principles, CEE programs can empower the workforce of the future to thrive in an increasingly complex and dynamic landscape. Discussions This study underscores the significance of Education 4.0 principles in shaping the future of CEE programs, emphasizing the crucial role of innovative learning approaches and technological integration in empowering the future engineering workforce in the Industry 4.0 era.